2015
DOI: 10.1007/s11738-015-1907-7
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect measurements of freezing tolerance: advantages and limitations

Abstract: The freezing tolerance of 69 accessions of field-grown, common wheat (Triticum aestivum) was assessed in three consecutive winters. To measure freezing tolerance directly, field-grown plants were subjected to a range of freezing temperatures in a controlled environment and plant regrowth was subsequently assessed. Indirect assessments of freezing tolerance, as measured by chlorophyll fluorescence transient measurements followed by a JIP-test (an in vivo measurement of the adaptive behavior of the photosyntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 28 publications
(56 reference statements)
5
25
0
Order By: Relevance
“…The OJIP test also provides information about the probability of the fate of absorbed light energy as well as detailed information on photosynthetic apparatus structure and function [ 8 ]. Recent studies of photosynthetic apparatus response to freezing based on the OJIP test have shown that the chlorophyll fluorescence techniques used to predict whole-plant freezing tolerance and, ultimately, winter hardiness are advantageous, but also have interesting limitations that make the reliability of the results dependent on certain conditions [ 15 17 ]. Although cold-induced changes in the photosynthetic apparatus are necessary for whole-plant cold acclimation [ 18 , 19 ], freezing tolerance in the field depends on many factors based on complex environmental responses [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The OJIP test also provides information about the probability of the fate of absorbed light energy as well as detailed information on photosynthetic apparatus structure and function [ 8 ]. Recent studies of photosynthetic apparatus response to freezing based on the OJIP test have shown that the chlorophyll fluorescence techniques used to predict whole-plant freezing tolerance and, ultimately, winter hardiness are advantageous, but also have interesting limitations that make the reliability of the results dependent on certain conditions [ 15 17 ]. Although cold-induced changes in the photosynthetic apparatus are necessary for whole-plant cold acclimation [ 18 , 19 ], freezing tolerance in the field depends on many factors based on complex environmental responses [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although cold-induced changes in the photosynthetic apparatus are necessary for whole-plant cold acclimation [ 18 , 19 ], freezing tolerance in the field depends on many factors based on complex environmental responses [ 20 ]. This complexity makes the results of chlorophyll fluorescence-based studies more difficult to understand, but can provide a unique opportunity to distinguish the effects of different environmental factors on freezing tolerance in the field [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, despite the fact that END does not bear the characteristics of the genuine winter cultivar suitable for European continental winters, it might be useful for further research oriented toward winter cultivars of afila type. Nevertheless, we still should keep in mind that further factors, such as the responsiveness to the photoperiod [42], also play a prominent part in winter resilience (for a review see, e.g., [43]), and that cold acclimation in laboratory conditions does not always reflect real winter hardiness [44]. Further tests are thus needed, including a winter survival test in the field, to support this idea.…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll fluorescence analysis is a non-destructive method that can be used to study the performance of the photosynthetic apparatus (PSII) in plants. The fluorescence parameter F v /F m expresses the maximum quantum yield of PSII and may be used as a stress indicator (Maxwell & Johnson, 2000), and several fluorescence parameters may be related to stress responses (Rapacz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%